Computational aspects to design iridium complexes as emitters for OLEDs. Issue 10 (20th July 2022) - Savitha Lakshmi, M.; Mahalakshmi, S.
Abstract : Depiction of red, green and blue emitters along with energy level diagram. Abstract : Organic light-emitting diode (OLED) devices fabricated using iridium complexes have attracted great attention from researchers for decades due to their high efficiency and opto-electronic properties. The choice of ligand and the chelate positions in the emitters play a vital role in the versatility of the device. Accordingly, computational studies have emerged as a reliable tool to provide experimental chemists with prior knowledge on the potential properties of designed complexes, enabling them to achieve higher efficiencies. They also provide essential information on the experimentally unexplored features of systems under study. In this review, we discuss in detail the computational aspects and parameters to be investigated theoretically for the design of potential iridium-based emitters for application in OLEDs. The results obtained for different systems can help arrive at a general conclusion about the modelling of emitters, where they can be designed computationally even before their synthesis as efficient emitters for application in OLEDs.